Capacidades dinâmicas, empreendedorismo e inovação no espaço rural: a agricultura familiar e a inovação no modelo de negócio - Carvalho, Alexandre Caldeirão (Universidade do Vale do Rio dos Sinos, 2022)
The family production model is present in 90% of rural properties in the world, these are responsible for the production of 80% of food. In a scenario dominated by the advent of information and communication technologies, it is important to discuss the nature of innovation in family farming, understanding that technology alone is not capable of providing operational or financial results, but is an instrument to be added to the model. according to the needs and capabilities of the rural producer, with a focus on productivity and sustainability of the family business. Thus, this research has as its central object of study innovation in rural areas, more specifically in family farms. The general proposition of the study is that innovation in family farms takes place managerially, not by the massive application of technological elements, but by changing the business model, where the rural property, understood as a firm, autonomously, innovatively, proactively, aggressive and taking risks scrutinizes the environment, perceives changes and internalizes information, adapting its strategy through the integration of external elements to its routines, in a process of elaborating alternatives to reconfigure its resources and transform its routines, adapting or changing its business model in a process of disruption or transformation, creating, delivering and capturing value. The study is characterized as explanatory, seeking to answer the question: What is the nature of innovation in family farms? The methodology used is quantitative, the independent variables analyzed in the study are dynamic capabilities and entrepreneurial orientation and the dependent variable is innovation in the business model. Two hypotheses were proposed, the first one affirms that Dynamic Capabilities are positively and significantly related to Innovation in the Business Model. The second states that there is a positive and significant relationship between Entrepreneurial Orientation and Innovation in the Business Model in family farms. The study sample consists of 260 family farms in the southern region of Rio Grande do Sul, more specifically in the Functional Planning Region 5 - RF5, where there are 31,098 agricultural establishments distributed in 21 municipalities. The sample was obtained through indications and references, using the non-probabilistic sampling technique called Snowball Sampling Technique. The composite reliability of all constructs was tested and the hypothesis test was performed using a multivariate regression analysis. The hypothesis that in the analyzed rural properties there is a positive and significant relationship between Entrepreneurial Orientation and Innovation in the Business Model was confirmed. The hypothesis that there is a relationship between Dynamic Capabilities and Innovation in the Business model was rejected, not being proven. However, the literature brings Dynamic Capabilities as an antecedent to innovation in the business model, so a third hypothesis was proposed, that dynamic capabilities are positively and significantly related to entrepreneurial orientation and this hypothesis was confirmed. Thus, the initial theoretical model of this thesis was partially rejected and another one emerged at the end, explaining business model innovation through entrepreneurial orientation and indirectly through dynamic capabilities that are related to entrepreneurial orientation. Therefore, it is concluded that for there to be innovation in the business model, it is not enough that the rural property has dynamic capabilities, but it is also necessary that it has an entrepreneurial orientation.
Keywords: Agricultura familiar; Capacidades dinâmicas; Orientação empreendedora; Inovação no modelo de negócio; Family farm; Dynamic capabilities; Entrepreneurship orientation; Business model innovation; ACCNPQ::Ciências Sociais Aplicadas::Administração